2021
DOI: 10.1186/s12902-021-00887-3
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea and 12-month weight loss in adults with class 3 obesity attending a multidisciplinary weight management program

Abstract: Background Although there is a strong association between obesity and obstructive sleep apnoea (OSA), the effects of OSA and CPAP therapy on weight loss are less well known. The aim of this study in adults with class 3 obesity attending a multidisciplinary weight management program was to assess the relationship between OSA and CPAP usage, and 12-month weight change. Methods A retrospective cohort study of all patients commencing an intensive multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…Our study addressed the widespread lack of research into the specific community‐based needs of individuals with severe obesity, and highlighted factors contributing to inadequacies within the current community‐based care model. While WMPs have been demonstrated to help patients attain a mean weight loss of around 6% at 12 months, weight regain is a major problem in this population 24–26 . Patients and clinicians in our study expressed concern for the lack of targeted support available once patients have left tertiary programs, identifying the loss of regular support from the clinic as a significant barrier to maintaining weight loss.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our study addressed the widespread lack of research into the specific community‐based needs of individuals with severe obesity, and highlighted factors contributing to inadequacies within the current community‐based care model. While WMPs have been demonstrated to help patients attain a mean weight loss of around 6% at 12 months, weight regain is a major problem in this population 24–26 . Patients and clinicians in our study expressed concern for the lack of targeted support available once patients have left tertiary programs, identifying the loss of regular support from the clinic as a significant barrier to maintaining weight loss.…”
Section: Discussionmentioning
confidence: 89%
“…While WMPs have been demonstrated to help patients attain a mean weight loss of around 6% at 12 months, weight regain is a major problem in this population. [24][25][26] Patients and clinicians in our study expressed concern for the lack of targeted support available once patients have left tertiary programs, identifying the loss of regular support from the clinic as a significant barrier to maintaining weight loss. Weightstigma, co-morbid mental health conditions, and social isolation have been reported to hinder engagement with existing communitybased services and/or support groups.…”
mentioning
confidence: 99%
“…This may possibly result from the multidisciplinary nature of the program, which included on site supervised exercise classes, and the attention provided to manage physical and mental health co-morbidities in these patients with higher EOSS scores [ 28 ]. We have also demonstrated that the presence of obstructive sleep apnoea as well as use of CPAP did not affect weight outcomes at 12 months in this cohort [ 30 ], nor did the presence of T2DM at baseline affect weight loss at 6 months [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…All patients were seen by a physician, dietitian and psychologist. The weight management program has been described in detail previously [ 28 , 29 , 30 , 31 ]. Dietary advice was personalised, which included but was not limited to advice for a 500 Kcal reduced diet, partial meal replacement and/or a low-calorie diet.…”
Section: Methodsmentioning
confidence: 99%
“…This was a cross-sectional study conducted in a hospital-based, publicly funded, multidisciplinary weight management program in Sydney, Australia, as previously described [ 42 , 43 , 44 , 45 ]. The study participants were recruited between February 2021 and December 2022, and they included all newly enrolled patients in the program who attended at least one physician appointment.…”
Section: Methodsmentioning
confidence: 99%